Implementation Of Character Education Through Religious Culture At Madrasah Aliyah Swasta Miftahussalam Medan - Simangunsong, Siti Amanda; Abdurrasyid, Abdurrasyid (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The aim of this research is to find out: (1) How Character Education is Implemented through Religious Culture at Madrasah Aliyah Miftahussalam Medan. (2) To find out the impact of the Implementation of Character Education through Religious Culture at the Miftahussalam Private Madrasah Aliyah Medan. The research methodology used is qualitative, with a focus on case studies. Data collection methods include observation, interviews, documentation. This research aims to describe the implementation of character religious education and its impact in madrasas. Therefore, the main focus of this research is how character education is implemented through religious beliefs. The results of this research show that the implementation of character education through religious culture at Madrasah Aliyah Miftahussalam Medan through religious activities and routine activities is running well. And the impact on students is to improve the spiritual quality of students, namely increasing faith and devotion as well as the values of activities carried out in madrasas which cannot be separated from efforts to get closer to the Creator.